PREVALENSI PENYAKIT JANTUNG ANAK DI RUMAH SAKIT UMUM DAERAH dr. ZAINOEL ABIDIN - Aslinar Aslinar; Eka Yunita Amna (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background: The greatest incidence rate is congenital heart disease which is a form of heart abnormalities that have been obtained since the newborn. PJB is a heart disease with a considerable number of events in Indonesia. The incidence of PJB in Indonesia is 8 per 1000 births. If the Indonesian population is 200 million, and the birth rate is 2%, then the number of PJB patients in Indonesia increases 32000 babies every year. Methods: This study is descriptive conducted on March 1 to June 30, 2017. Respondents are 158 respondents by using medical records. Results: In general, the results showed that the prevalence of heart disease in children in the Regional General Hospital dr. Zainoel Abidin Banda Aceh Year 2017, which is in congenital heart disease is 139 respondents (88.0%). Conclution: Based on the above results it is expected that the mother in order to maintain the condition of the ananya to limit the activity, stress for heart work can be rested and always mengontol child's heart condition at the center of health services needed.Keywords: Heart, Disease, Children